Pattern of retreat and related morphological zones of Gangotri Glacier, Garhwal Himalaya, India. (15th July 2017) - Singh, Dhruv Sen; Tangri, Anjani Kumar; Kumar, Dhirendra; Dubey, Chetan Anand; Bali, Rameshwar
Abstract: Gangotri, one of the longest valley glaciers of the Garhwal Himalaya has attracted global attention due to rapid rate of retreat. It is characterized by supraglacial moraines, supraglacial lakes, intensive crevasses, active and inactive tributary glaciers which were mainly responsible for the enhanced recession rate of the glacier. However, contrary to the generally accepted notion of "Global Warming", the Gangotri Glacier has been experiencing diminishing rates of retreat during last five decades. High retreat rate of 38 m/y observed in 1970s has been reduced in 1980s and maintaining the similar trend in the recent decades with reduced rate of retreat around 10 m/y in 2015. The measurement of Equilibrium Line Altitude (ELA) and ablation area over the last few decades also explained that the response of Gangotri Glacier is not in pace with the global warming trend. Glacial (Gl) and glacio-fluvial (Gf) features have been identified as the marker morphological zones which provides information about pattern of retreat and ELA. The sediment size decreases whereas sorting, roundness and percentage of matrix increases from Gl-Gf zone. The glacial zone contains the primary sediments and provides information about the pattern of retreat and ELA. The glacio-fluvial outwash plain exhibits modification of glacial signatures and often contains secondary sediments. Further, different rate of fluctuation observed in different glaciers indicate that the glaciers are not uniformly responding with change in climatic conditions, especially with respect to global warming. Such observations and present study suggest that fluctuation of a glacier is not only controlled by global warming induced temperature but also governed by characteristics of the glacier and local morphological factors. Hence, the analysis of the pattern of retreat, ELA and retreat related morphological zones, provide real information and precise glacial history of the area.